P-63 Implementation of a palliative care electronic patient record shared with gps, dns and the out of hours service. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Salt, Susan; Bonnis, Marie; Parkes, Nicky; Green, Debra; Wylde, Carol; Murphy, Victoria; Lord, Bridget
Abstract : Aims of the Project: To move to an electronic patient record across all clinical departments accessible to local community services enabling access to real time information about a patient's care and condition shared across the hospice, general practice, district nursing services and out-of-hours service Enable hospice staff to remotely access a patient's up-to-date record enabling advice given and care delivered to be recorded without having to find a set of case notes or returning to base Reduced amount of telephone and fax traffic between primary care and the hospice around clarifying care, medication and other key factors such as known allergies Saving time on administration and record keeping to enable more clinical time. Over a period of nine months using a change management approach an instance of the electronic patient record (EMIS) was developed for each clinical team, based on a common holistic assessment. At all stages staff engagement and communication was a high priority. Roll out was staggered over a one month period with GO LIVE starting with the smaller day time services, to iron out any teething problems, using the lessons learnt in the bigger 24-hour services including both an adult and children's in-patient unit. (For patient confidentiality reasons the bereavement service was excluded from the whole process.) Outcomes: Having completed level 2 of the information governance toolkit and compliance with information governance requirements locally all healthcare professionals in the community over 24hours are able to access real time information about all patients known to the specialist palliative care service The specialist palliative care service can access the records of patients referred to them and those where advice is requested Accuracy of medication histories, compliance and allergy recording has improved The amount of time lost by clinical staff making phone calls has reduced by a third.